2011
DOI: 10.1002/ar.21251
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Differentiation and the Neuroendocrine Hypothesis of Autism

Abstract: The phenotypic expression of autism spectrum disorders varies widely in severity and characteristics and it is, therefore, likely that a number of etiological factors are involved. However, one finding which has been found consistently is that there is a greater incidence of autism in boys than girls. Recently, attention has been given to the extreme male hypothesis-that is that autism behaviors are an extreme form of typical male behaviors, including lack of empathy and language deficits but an increase in so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 89 publications
0
12
0
Order By: Relevance
“…The differential contribution of the two orienting responses to the prediction of sex has been supported by logistic regression analysis showing an acceptable percentage of correctly classified men and women only when both responses were entered in the equation as predictor variables. The sex differential pattern of the LPP reflecting women’s greater response to social scenes and the ECR reflecting men’s greater (defense preparatory) response to non-social scenes might support the evolutionary view on the propagation of mammalian species supposing the female gender being responsible for “tending and befriending” and the male gender for “defending” [38] . The stronger cardiac orienting to nonsocial information in males than in females might also be in line with the male brain hypothesis proposing the more systemizing male brain to be more prepared for the processing of nonsocial events and to have a greater need for a predictable environment [39] .…”
Section: Discussionmentioning
confidence: 68%
“…The differential contribution of the two orienting responses to the prediction of sex has been supported by logistic regression analysis showing an acceptable percentage of correctly classified men and women only when both responses were entered in the equation as predictor variables. The sex differential pattern of the LPP reflecting women’s greater response to social scenes and the ECR reflecting men’s greater (defense preparatory) response to non-social scenes might support the evolutionary view on the propagation of mammalian species supposing the female gender being responsible for “tending and befriending” and the male gender for “defending” [38] . The stronger cardiac orienting to nonsocial information in males than in females might also be in line with the male brain hypothesis proposing the more systemizing male brain to be more prepared for the processing of nonsocial events and to have a greater need for a predictable environment [39] .…”
Section: Discussionmentioning
confidence: 68%
“…According to the EMB individuals with ASD are characterized by impairments in empathizing while having intact or superior systemizing skills. Several studies provide supporting evidence for the empathizing-systemizing theory of psychological sex differences and the related EMB theory ( Baron-Cohen et al, 2003 ; Lawson et al, 2004 ; Wakabayashi et al, 2007 ; Aiello and Whitaker-Azmitia, 2011 ; Brosnan et al, 2012 ). For example, Wheelwright et al (2006) examined the EMB in a large UK sample that compared students (723 males, 1038 females) to adults with ASD (69 males, 56 females) and found that the majority (62%) of adults with ASD had an extreme male brain type (S > > E), compared to only 5% of typical males and 0.9% of typical females.…”
Section: Introductionmentioning
confidence: 82%
“…In contrast both males and females retained normal sociability and spatial learning and memory, despite the enhanced anxiety. These encountered neurobehavioral features were reminiscent of an anxiety disorder and/or attention deficit disorder that constitute neuropsychiatric conditions (Aiello and Whitaker-Azmitia, 2011; Pfaff et al, 2011). Retention of normal sociability and spatial learning and memory perhaps rules out conditions akin to autism spectrum disorders or other cognitive dysfunctional disorders (Mair et al, 1991; Silverman et al, 2011; Tanda et al, 2009).…”
Section: Discussionmentioning
confidence: 99%